Pt@ZnCo2O4 Microspheres as Peroxidase Mimics: Enhanced Catalytic Activity and Application for L-Cysteine Detection - Shuqi Liao; Weisen Deng; Feng Yang; Jutao Zhou; Ling Wu; Donghong Yu; Zhong Cao (Molecules)
Compared to natural enzymes, the development of efficient artificial simulated enzymes, such as those based on bimetallic materials with high catalytic activity and good stability, is an important way until now. Herein, we employed ZnCo2O4 microspheres as carriers to synthesize Pt-doped composites with different amounts using a one-pot method. The morphology and structure of the synthesized materials were characterized using XRD, SEM, BET, FT-IR, XPS, and Zeta potential techniques. It was found that Pt0 adhered well to the surface of ZnCo2O4 microspheres, with a 12.5% Pt doped ratio exhibiting abundant oxygen vacancies, excellent substrate affinity, and high peroxidase-like activity. Using fluorescent probes and electrochemical methods, the peroxidase-like catalytic mechanism has been explored that Pt@ZnCo2O4 microspheres can accelerate the electron transfer between H2O2 and 3,3′,5,5′-tetramethylbenzidine (TMB). Based on the optimal loading ratio of 12.5% of Pt@ZnCo2O4, a colorimetric sensor for visual detection of L-cysteine (L-Cys) was constructed, exhibiting a wide linear range of 0.1~50 µM and a low detection limit of 0.0163 µM. The sensor possesses good selectivity, reusability, and usage stability, which can be well applied to the determination of L-Cys in health product capsules with recovery rates of 96.9%~103.7% and RSD of 1.07%~6.50%. This work broadens the application prospects of spinel materials such as ZnCo2O4 in the field of biological analysis and also provides inspiration for the development of new artificial simulated enzymes.